Behind the curtain of scholarly publishing : editors in writing studies - Giberson, Greg; Schoen, Megan; Weisser, Christian R., 1970- (Utah State University Press, 2022)
"Provides new and seasoned scholars with behind-the-scenes explorations and expositions of the histories of scholarly editing and the role of the scholarly editor from the perspectives of current and former editors from important publication venues within the field" --